Analysis of adherence of Streptococcus defectivus and endocarditis-associated streptococci to extracellular matrix. - Tart, R C (1991)
Pathogenesis of nutritionally variant streptococcal (NVS) endocarditis initiates with bacterial attachment to and colonization of the damaged heart valve surface. Underlying extracellular matrix (ECM) exposed to the environment during damage to cardiac endothelium provides additional receptors that could be involved in bacterial adherence. The ability of NVS and endocarditis-associated streptococci to bind ECM was investigated by using an enzyme-linked immunosorbent assay system that incorporated ECM secreted by baby hamster kidney and human umbilical vein endothelial cells in culture. Streptococcus defectivus, the major species isolated from NVS endocarditis cases, bound ECM of fibroblasts and endothelial cells, indicating that the ECM molecule involved in the binding was a common constituent of diverse matrices. The specific binding of S. defectivus to ECM was demonstrated by saturation binding and specific antibody inhibition studies. Of the 15 S. defectivus strains analyzed, 13 bound ECM, whereas Streptococcus adjacens and NVS serotype III strains were unable to bind the matrix. This selective binding suggested that S. defectivus binds to heart valves through a mechanism different from those of other NVS in subacute bacterial endocarditis. A survey of non-NVS streptococcal endocarditis isolates demonstrated that S. mutans, S. mitis, S. sanguis, and S. faecalis also bound ECM, whereas other viridans species were unable to bind the matrix.